Transformation in pharmacy education to meet the current demand - Zin, Che Suraya (2019)
Around the world, pharmacy education is undergoing significant transformation to advance the practice of pharmacy and improve patient outcomes. Pharmacists are moving beyond dispensing medications toward more advanced services such as comprehensive medication safety systems, collaborative drug therapy management and improving transitions of care.